RESEÑA de : Anne J. Cruz & María Gallistampino (eds.), Early Modern HabsburgWomen: Transnational Contexts, Cultural Conflicts, Dynastic Continuities. Farnham, Ashgate, 2013, 294 pp. IS BN: 978-1-4724-1164-8. - Martínez López, Rocío (Espacio Tiempo y Forma. Serie IV, Historia Moderna, 2015)
RESEÑA de : Anne J. Cruz & María Gallistampino (eds.), Early Modern HabsburgWomen: Transnational Contexts, Cultural Conflicts, Dynastic Continuities. Farnham, Ashgate, 2013, 294 pp. IS BN: 978-1-4724-1164-8.